Influência de solos de diferentes texturas no desenvolvimento de plantas de Eucalyptus urograndis submetidas a déficit hídrico - Pereira, Maria Renata Rocha [UNESP]; Klar, Antonio Evaldo [UNESP]; Filho, André Luiz Melhorança [UNESP]; Rodrigues, Andréia Cristina Peres [UNESP]; Silva, Magali Ribeiro da [UNESP] (My University, 2008)
The studies were developed with plants of Eucalyptus urograndis under greenhouse conditions, at Paulista State University (UNESP), Botucatu - SP, from March to July, 2005. The objective was to evaluate hydric stress influence on morphological and physiological characteristics of plants in clayay (1) and medium (2) soil texture. Two water treatment were used: -0.03 and -1.5 MPa minimum soil water potentials (□w). Plants from soil 2 and - 1.5MPa showed 43% reduction on leaf área, 34% on base stem diameter, 54% on aerial vegetal dry matter and plants from soil 1 presented 42.3% reduction on leaf área, 39,5% base stem diameter and 42% dry matter root reduction in relation to -0.03 MPa. The lowest leaf water potential (□f) value was-17.166 MPa on □w = -1.5 MPa and soil 2 and the greatest one on soil 1 and □w = -0.03 MPa., -6.766 MPa. The treatment -0.03MPa showed about 11,3% higher transpiration values than those plants from -1.5MPa. The higher Rs value (2.149 s.cm-1) occurred on plants under -1.5MPa and soil 2. There was significant correlation between Tf and Rs, and the treatmens from medium soil were more sensitive, reaching until 32°C.
Different soil hydric deficit and texture influence on Eucalyptus urograndis plants
Keywords: Hydric stress; Transpiration water potential and stomatal resistance; Morphology; Physiology; Plants (botany); Soils; Stresses; Transpiration; dry matter; morphology; physiological response; stomata; transpiration; water treatment; Botucatu; Brazil; Sao Paulo [Brazil]; South America; Eucalyptus; Eucalyptus urograndis